Quantificação do percentual de glaciamentono camarão branco do pacífico(Litopenaeus vannamei) congelado: uma nova metodologia - Rebouças, Lucas de Oliveira Soares (Brasil, 2015)
Due to the high perishability of seafood, one of the main industry concerns is to improve conservation technologies, reaching a final product of good quality. Among the various methods used, it highlights the glazing process after freezing, which provides greater stability and shelf life for the product. On the other hand, some abuses have been reported regarding the water excess in glazed products, characterized as economic fraud. In this context, the aim of this study was toevaluate the effectiveness of official methods to quantify the glazing percentage in frozenwhite Pacific shrimp (Litopenaeus vannamei) samples, with different glazing percentages. Based on the obtained resultsasuggestion ofa new simpler and more efficient methodologyis a goal. Samples of peeled shrimp were subjected to glazing process (15%, 30%, 40%, 50% and 60%). The glazingpercentage was quantified based on methodologies of INMETRO, MAPA, CODEX, AOAC/NIST and through the proposal suggested in thiswork. The official methods were inefficient in quantifying the glazing percentage, especially with regard to samples containing high glazing percentages. The methodology proposed results were closer to the values of the glazing percentage of frozen shrimpsamples, confirming that the methodology can be an alternative to be used by the inspectors, after collaborative study validation of the methodology
Measurement of glazing percentage in frozen pacific white shrimp (Litopenaeus vannamei) - a new methododology
Keywords: Pescado; Qualidade; Congelamento; Glaciamento; Fraude; Seafood; Quality; Freezing; Glazing; Fraud; CIENCIAS AGRARIAS::ZOOTECNIA